35 miles from shore : the ditching and rescue of ALM flight 980 - Corsetti, Emilio (Odyssey Pub., 2008)
On May 2, 1970, a DC-9 jet with 57 passengers and a crew of six departed from New York's JFK International Airport en route to the tropical island of St. Maarten, but four hours and 34 minutes later the flight ended in the shark-infested waters of the Caribbean. It was, and remains, the only open-water ditching of a commercial jet. The subsequent rescue of survivors took nearly three hours and involved the coast guard, navy, and marines. This gripping account of that fateful day recounts what was happening inside the cabin, the cockpit, and the helicopters as the crews struggled against the we.